Пропріоцептори деяких м’язів грудної кінцівки крота європейського Talpa europaea L., 1758 - Кедров, Б. Ю.; Гуменна, О. (Видавництво НДУ ім.М. В. Гоголя, 2007)
Using the light microscopy methods and the hematoxylin-eosin staining, the 345 serial histological sections from m. teres major and m. pectoralis superfacialis pars anticus of European mole were examined. In m. teres major the 21 neuromuscular spindles (length - 1001 ± 107 μm, diameter in the equatorial zone - 37,4 ± 3,1 μm) were found. And in m. pectoralis superfacialis pars anticus we revealed only the 8 neuromuscular spindles (1054 ± 102 μm, diameter in the equatorial zone - 42.0 ± 5.5 μm). All spindles has 1-3 nuclear bag fibers and 2 nuclear chain fibers. The density of the neuromuscular spindles in the thickness of the muscles was uniform.
Keywords: Проприоцепторы; мышечные веретена; proprioceptors; muscle spindles